Route of Antigen Presentation Can Determine the Selection of Foxp3-Dependent or Foxp3-Independent Dominant Immune Tolerance - Agua-Doce, Ana (2018)
This deposit is composed by a publication in which the IGC' authors have had the role of collaboration (it's a collaboration publication). This type of deposit in ARCA is in restrictedAccess (it can't be in open access to the public), and could only be accessed by two ways: either by requesting a legal copy to the author (the email contact present in this deposit) or by visiting the following link: http://www.jimmunol.org/content/200/1/101.long#ack-1